Chiliadenus iphionoides: From chemical profiling to anticancer, antioxidant, α-amylase, and α-glycosidase activities. - Odey Bsharat; Yousef Salama; Nisreen Al-Hajj; Nawaf Al-Maharik (PLoS ONE)
Recently, essential oils (EOs) have garnered attention for their biological properties as a source of natural compounds with anticancer, antibacterial, and antioxidant effects. Chiliadenus iphionoides (Boiss.& Blanche) Brullo is a fragrant aromatic species indigenous to Palestine and the neighboring countries. It is utilized by the Bedouins for the treatment of many ailments. This study aimed to analyze the chemical composition of essential oil extracted from the desiccated leaves of Chiliadenus iphionoides (Boiss.& Blanche) Brullo and to assess its in vitro antioxidant, anticancer, and α-amylase and lipase inhibitory activities. The EO obtained during hydrodistillation was analyzed using gas chromatography-mass spectrometry to ascertain their chemical composition. GC-MS analysis of the EO from dried Chiliadenus iphionoides (Boiss.& Blanche) Brullo leaves identified 47 compounds, comprising 98.81% of the total oil. The predominant constituents included cresol methyl ether (52.93%), ethyl 2-octynoate (14.36%), epi-α-cadinol (6.56%), 1,8-cineole (4.25%), and 7-epi-α-eudesmol (3.66%). The EO exhibited significant antioxidant activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) with an IC50 value of 19.83 ± 0.99 μg/mL. Nevertheless, it exhibited limited lipase activity and subpar α-amylase activity. Chiliadenus iphionoides (Boiss.& Blanche) Brullo EO exhibited significant cytotoxicity against B16F10 and MCF-7 cancer cell lines, with IC50 values of 8.74 ± 0.11 and 13.68 ± 0.17 μg/mL, respectively. The combination of the anticancer medication Taxol (10 ng) with Chiliadenus iphionoides (Boiss.& Blanche) Brullo EO at concentrations of 25 μg/mL and 50 μg/mL significantly enhanced the inhibitory efficacy of Taxol against MCF-7 and B16F10 cells.